(untitled) (Konferensiyalar | Conferences, 2024)
It is important that, there are different methods for teaching English. In teaching English, it is necessary to use and pay attention to new ways for developing students’ speech. Hovewer, several classic schools are still trying to use old books and methods. At the same instant, they will be some problems, and they also do not satisfy their English level and the quality of the lessons. This article purposes to improve students’ language ability and to discuss some interesting and useful methods.